Vanishing of Brauer groups of moduli stacks of stable curves - Sebastian Bartling; Kazuhiro Ito (Forum of Mathematics, Sigma)
We show that the cohomological Brauer groups of the moduli stacks of stable genus g curves over the integers and an algebraic closure of the rational numbers vanish for any